2017
DOI: 10.2214/ajr.16.17125
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Clinicopathologic and Dynamic Contrast-Enhanced MRI Findings for Tumor Response to Neoadjuvant Chemotherapy in Triple-Negative Breast Cancer

Abstract: Homogeneous enhancement of tumors on pre-NAC MRI and the presence of a concentric shrinkage pattern after NAC are associated with pCR in patients with TNBC. Residual tumor sizes on MRI and surgical specimens tended to show a stronger correlation in the pCR group or the concentric shrinkage group than in the non-pCR group or the dendritic shrinkage group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
0
24
0
2
Order By: Relevance
“…A previous study showed that TNBC was more uneven on dynamic contrastenhanced MRI (29). Although the imaging modes used were The clinicopathology of tumors can reflect tumor biology and affect the outcome of chemotherapy in TNBC patients (30)(31)(32)(33). Our study found that the TNBC histological grade of the high TIL group was lower than that of the low TIL group (84%).…”
Section: Discussionmentioning
confidence: 46%
“…A previous study showed that TNBC was more uneven on dynamic contrastenhanced MRI (29). Although the imaging modes used were The clinicopathology of tumors can reflect tumor biology and affect the outcome of chemotherapy in TNBC patients (30)(31)(32)(33). Our study found that the TNBC histological grade of the high TIL group was lower than that of the low TIL group (84%).…”
Section: Discussionmentioning
confidence: 46%
“…Published studies with this goal are limited by small cohort sizes 18,2022,24,25 . Furthermore, most of these studies used RECIST to measure response 18,21,24,25 , even though pCR is highly correlated with event-free survival and overall survival 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies using pathologic assessment to determine response have varying definitions of pCR 20,22 . In some of these studies patients with positive lymph nodes 20,22 , residual DCIS 20,22 , or even residual invasive carcinoma in the breast 22 are categorized as having pCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intratumoral heterogeneity is associated with prognosis [9,10]. A study showed a positive relationship of tumor heterogeneity with recurrence-free survival in breast cancer patients [11].…”
Section: Introductionmentioning
confidence: 99%